2017
DOI: 10.1080/13557858.2017.1315373
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the health of Spanish Roma people and what has been done to improve it? A scoping review

Abstract: There are few publications related to the health of the Roma community in Spain and even fewer related to health interventions and outcomes. Those that are available have focused on areas such as child health or infectious disease outbreaks. It is important to promote health interventions in Roma communities and longitudinal studies that include a comprehensive vision and account for the social determinants of health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
0
28
0
3
Order By: Relevance
“…It has been thoroughly demonstrated that Roma people are overrepresented in marginalized communities and live in unhealthy environments, and their health behaviour is significantly less favourable than that of the non-Roma population [ 38 , 64 , 65 , 66 ]. The health of Roma can be considered as global ill health [ 1 ], based not only on the burden of rare and infectious diseases [ 4 , 5 ], but also on chronic non-communicable diseases of high public health importance, such as cardiometabolic diseases, which are significantly higher among them than in the majority population [ 7 , 8 , 9 , 11 , 12 , 13 , 67 ]. In addition, the access of Roma people to health care is also impaired, resulting in a broad spectrum of unmet health needs [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been thoroughly demonstrated that Roma people are overrepresented in marginalized communities and live in unhealthy environments, and their health behaviour is significantly less favourable than that of the non-Roma population [ 38 , 64 , 65 , 66 ]. The health of Roma can be considered as global ill health [ 1 ], based not only on the burden of rare and infectious diseases [ 4 , 5 ], but also on chronic non-communicable diseases of high public health importance, such as cardiometabolic diseases, which are significantly higher among them than in the majority population [ 7 , 8 , 9 , 11 , 12 , 13 , 67 ]. In addition, the access of Roma people to health care is also impaired, resulting in a broad spectrum of unmet health needs [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although restrictions exist on collecting statistical data on health and its determinants by ethnic status in the countries where Roma populations are most concentrated (Southern, Central, and Eastern European countries) [ 2 , 3 ], increasing amounts of data from ethically appropriate one-off surveys are available and show that the health of Roma is much worse than that of the general population [ 1 ]. These studies are almost exclusively descriptive ones on the prevalence of certain diseases, especially infectious and certain genetic diseases [ 1 , 4 , 5 ], and of health determinants [ 6 , 7 , 8 , 9 ], especially cardiovascular risk factors [ 10 , 11 , 12 ], while comprehensive exploratory studies are missing.…”
Section: Introductionmentioning
confidence: 99%
“…All of these problems are reflected in the questionable effectiveness of Roma-targeted health interventions [3,4,28,29], showing that program elaboration, monitoring, and evaluation require the development of currently applied epidemiological methods. At present, responsible policy-makers face a scarcity of useful data on the population-level health impact of Roma ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…En ese sentido, se trata de una investigación aplicada y orientada hacia la mejora de la intervención. En un análisis de la literatura publicada sobre la salud de la población gitana (Fernández, Pesquera y Prieto, 2017), se subrayaba precisamente la escasez de este tipo de publicaciones que no se centran únicamente en analizar la salud de la población gitana, sino que orientan el foco hacia el funcionamiento de los programas y los modelos profesionales. Aunque el modelo de competencia cultural ha recibido diferentes críticas en la literatura científica, se considera que sigue siendo de gran utilidad para el abordaje de las desigualdades en salud (Kirmayer, 2012), siempre y cuando se tengan en cuenta algunas cuestiones ya referidas en la introducción, como evitar una concepción esencialista de la cultura (Jenks, 2011) o no desviar la atención del resto de determinantes sociales de la salud (Fassin, 2011).…”
Section: Ejes Para La Mejora De La Competencia Intercultural Profesionalunclassified